GRANULAR CELL ASTROCYTOMA - Batool, Ayma; Azra Bashir,; Saira Javed,; Samina Zaman,; Akhtar Sohail Chughtai, (Journal of Ayub Medical College Abbottabad, 2023)
Granular cell astrocytoma (GCA) is a rare glial neoplasm composed of abundant granular cytoplasm gives immunoreactivity for GFAP and S100 stains. We report a case of GCA in a 64 years old male presented with history of fits, right sided weakness and loss of consciousness. The microscopy showed sheets of large cells with abundant eosinophilic granular cytoplasm. No high-grade features were seen. Its differential diagnosis includes most of the benign histiocytic conditions. Granular cell astrocytoma has an aggressive clinical course and its survival rate is less than 1 year. That's why early correct diagnosis is very essential.